SNP Variation of RELN Gene and Schizophrenia in a Chinese Population: A Hospital-Based Case–Control Study - Luo, Xia; Chen, Si; Xue, Li; Chen, Jian-Huan; Shi, Yan-Wei; Zhao, Hu (Frontiers in Genetics, 2019)
Aims: We aimed to explore whether RELN contributes to the vulnerability and the severity of clinic symptoms of schizophrenia in Chinese population. Methods: Case-control association analyses of 30 representative single nucleotide polymorphisms screened according to specific programs based on bioinformatics tools and former researches, as well quantitative trait loci analyses with SNPs and psychiatric symptoms evaluated by the positive and negative symptoms scale were conducted in an adult Han Chinese population from Southern China. Results: A 4-SNP haplotype consisting of rs362814, rs39339, rs540058 and rs661575 was found significantly associated with schizophrenia even after Bonferroni correction (χ2=29.024, P=6.42E-04, Padjustment=0.017), and the T-C-T-C haplotype turned to be a protective factor for schizophrenia (OR=0.050, 95%CI=0.004-0.705). Moreover, the 4-SNP haplotype showed significant association with G16 (active social avoidance) after false discovery rate correction (χ2=28.620, P=1.697E-04, Padjustment=0.025). In addition, P7 (hostility) demonstrated to be related to the haplotype consisting of rs2229864, rs2535764 and rs262355 (χ2=31.424, P=2.103E-05, Padjustment=0.019) in quantitative trait loci analyses. Conclusions: Overall, this study showed several positive associations between RELN and schizophrenia as well psychiatric symptoms, which not only supports the proposition that RELN is a susceptibility gene for schizophrenia but also provides information on genotype-phenotype correlation for schizophrenia in Chinese population. However, as the small sample of this study, further investigations among larger samples are required.